Efforts to Build a Culture of Transformational Leadership in Islamic Education Institutions - Zaenal Arifin; Binti Maunah (Indonesian Journal of Islamic Education Studies (IJIES), 2020)
This article aimed to explain how to civilized transformational leadership in Islamic educational institutions. Discussions about transformational leadership have recently become lively to be discussed at the Islamic Education Institution (LPI). This is because Islamic educational institutions have prophetic religious spirits that are considered appropriate to be developed at LPI. Bernard Bass's transformational leadership theory becomes the main theoretical framework. The characteristics and goals of transformational leadership are in line with the conception of prophetic leadership in Islam. Therefore, to cultivate transformative leadership in LPI, it needs to be preceded by the creation of an organizational culture that implements prophetic values. Then to realize it can use three civilizing models, namely; structural models, formal models and mechanical models.